Dioxin‐like contaminants are no longer a risk to the American eel (Anguilla rostrata) in Lake Ontario. (9th January 2018) - Hoobin, Sharilyn J.; Byer, Jonathan D.; Alaee, Mehran; Brown, R. Stephen; Hodson, Peter V.
Abstract: The embryotoxicity of extracts of American eels ( Anguilla rostrata ) was measured to determine whether maternally derived contaminants contribute to the declining recruitment of eels to Lake Ontario. Sexually maturing, large yellow and silver eels were sampled in 2007 and 2008 from 5 locations in eastern Canada, including Lake Ontario; positive controls included eels from the Hudson River, United States, and Canal Dessel‐Schoten, Belgium (European eel, Anguilla anguilla ). Japanese medaka eggs were injected immediately after fertilization with 1 or 10 nL of eel extract and, after 12 d, scored for signs of toxicity. Eel extracts did not cause dioxin‐like embryotoxicity, reflecting the low concentrations of total dioxin equivalents measured chemically in these same extracts. Embryo mortality and reduced hatching success at high doses of eel extracts may reflect the bioaccumulation of legacy or emerging chemicals of concern. The results were consistent with long‐term trends of declining concentrations of persistent organic pollutants (POPs) in tissues of eels and other fish species from Lake Ontario, trends of declining embryotoxicity of eel tissue extracts, and recent increases of recruitment of juvenile eels to Lake Ontario. If dioxin‐like compounds contributed in the past to the decline of recruitment and abundance of American eels in Lake Ontario, these data suggest that recruitment should recover, following the same trends as the recovery of lake trout reproduction in Lake Ontario. Environ Toxicol Chem 2018;37:1061–1070. © 2017 SETAC